The Shrinking City as a Testing Ground for Urban Degrowth Practices - Hermans, Maurice (2024)
To inform and operationalize an urban degrowth agenda, more systematic and larger-scale experimentation with degrowth practices is needed. The aim of this study was to explore the suitability of shrinking cities as testing grounds for urban degrowth practices. To answer this question, we analyzed two cases, both urban greening initiatives, located in the shrinking urban region of Parkstad Limburg, in the Netherlands. The cases show that in a shrinking city, with a large surplus of urban land and long-term vacancy and demolishing of buildings, there is literally abundant “room” to experiment with alternative ways and types of urban land use. There is also interest on the side of the local government in alternatives to the conventional approaches to urban planning and development. As both cases can be interpreted as “experiments with urban degrowth practices,” it can be concluded that shrinking cities offer ample opportunities for urban degrowth experiments. The lessons learned from the two studied cases are not very positive concerning the wider feasibility of the tested degrowth practices, but as experiments, the cases can be considered successful. This is because they provided a better understanding of the conditions required for the implementation and upscaling of these practices, also in growing cities. To inform and operationalize an urban degrowth agenda, we, therefore, recommend more research on cases in shrinking cities that can be interpreted and analyzed as experiments with urban degrowth practices.